Pengembangan Media Pembelajaran Video Animasi Menggunakan Aplikasi Powtoon Untuk Materi Perkalian Dengan Metode Matematika Gasing (Gampang, Asyik, Dan Menyenangkan) - Galang Mi’raj Fatanna; Muhammad Amin; Bobbi Rahman (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Instructional media plays a crucial role in achieving educational objectives. Educators need to develop teaching strategies using various appropriate media and learning resources. Currently, GASING mathematics instructional media only consists of modules, PowerPoint, and teaching aids. This indicates the untapped potential in utilizing instructional media such as animated videos as engaging and effective learning tools. Based on this issue, the researcher employed the GASING method in the subject of mathematics, specifically focusing on multiplying 2-digit numbers by 1-digit numbers. This study aims to ascertain the development process and feasibility of animated videos using Powtoon. These animated videos were developed using the ADDIE model. Based on validation results by language experts, an average of 98.33% was obtained, while content experts yielded an average percentage of 78.18%. Furthermore, media experts achieved an average percentage of 90.67%, and individual trials (One to One) resulted in an average percentage of 85.64%. Based on the validation results by experts, it can be concluded that animated video instructional media using Powtoon in mathematics with the GASING method as the developed instructional media is highly suitable for field use, as evidenced by the average percentage of feasibility obtained being 88.21% (very feasible).